Islamic Performance of Administrative Staff at Higher Education in Riau Province - Safarin (Nalar Global Foundation, 2021)
This study aims to find the concept of coaching the performance of administrative staff, especially in higher education institutions that have a vision of integrating knowledge. The research was conducted at universities with a vision of integrating knowledge, Islamic universities with a non-integration vision of science, and non-religious universities. Respondents who were involved as samples were 424 staffs with an Ex Post Facto approach, namely research conducted after an incident occurred to find causes that allow changes in behavior, symptoms or phenomena caused by an event, behavior, symptom. The data is processed through Structural Equation Modeling (SEM) from the AMOS statistical software package. The results showed that religiosity had a positive effect on Internalization of Organizational Vision (0.01), Spiritual Ethos had no effect on Internalization of Organizational Vision (0.89), Internalization of Organizational Vision had no effect on Islamic Performance (0.00), Religiosity had no effect on Islamic Performance (0.24), and Ethic Spiritual has a positive effect on Islamic Performance (0.00). The research findings also show differences between Islamic universities Vision Integration of Science and Islamic Higher Education Vision of non-integration of science, and non-religious higher education, in Islamic universities. Religious vision (Integration of Science) is not required Internalization of organizational vision as a mediator of spiritual ethos on Islamic performance while at other universities it is needed.